Estado sombra: lo inconsciente en las críticas al Estado paternalista desde Carl Jung - Mastro Puccio, Fernando del (2015)
With the present paper we seek to use Carl Jung´s theoretical approach to the “Projection of the Shadow” as a framework to reveal posible unconscious motivations in our critiques to the Government´s paternalistic attitudes and regulations. Our proposal is that certain aspects of ourselves as individuals and society, which we do not like and do not accept (our Shadow), are seen exclusively as attributable to the Government. We argue that this unconscious dynamic limits our understanding of ourselves and prevents us to comprehend the essence of paternalism, both in our relation with the Government and in our daily life. We do not intend to discuss the logical or empirical validity of the arguments against this form of Government but to point out that those arguments might be influence by unconscious motivations.